UJI VIABILITAS DAN VIGOR BENIH BEBERAPA VARIETAS PADI (Oryza sativa L.) YANG DIPRODUKSI PADA TEMPERATUR YANG BERBEDA SELAMA KEMASAKAN - Cut Nur Ichsan (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2006)
Test of Viability and Seed Vigor of Several Rice Varieties Produced in Difference Temperaturs During Ripening Stage Cut Nur Ichsan ABSTRACT Research concerning effect of variety and temperature at ripening stage on viability and seed vigor has been conducted in seed technology laboratory of Agriculture Faculty, SyiahKualaUniversityfrom March 2004 until August 2004. The aim of the research was to evaluate seed viability and vigor of seed due to variety and ripening temperature. A factorial completely randomized design was used in this research. The rice varieties used were cisantang, kalimas, ciherang, widar and IR 64. The temperatures of ripening stage were : 27-32 oC and 30-38 oC. Observed variables were growth potency, germination rate, growth speed, growth uniformity, germination time for 50 % seed, dry weight of normal seedling. Result showed that variety and ripening stage temperature did not have significant effect on viability and vigor of rice seed.